Infrared study of the MoO3 doping efficiency in 4,4′-bis(N-carbazolyl)-1,1′-biphenyl (CBP) - Glaser, Tobias; Beck, Sebastian; Lunkenheimer, Bernd; Donhauser, Daniela; Köhn, Andreas; Kröger, Michael; Pucci, Annemarie (Organic electronics, 2013)
Electrochemical doping produces clear changes in the vibrational spectra of organic semiconductors as we show here for the system molybdenum oxide (MoO3) doped into the charge transport material 4,4′-bis(N-carbazolyl)-1,1′-biphenyl (CBP). Based on density-functional theory (DFT) calculations of vibrational spectra, the new spectral features can be attributed to the CBP cation that forms as a result of electron transfer from CBP to MoO3. The intensity of the new vibrational lines is a direct measure for the probability of charge transfer. MoO3 agglomerating within the CBP matrix limits the active interface area between the two species. The appearance of a broad electronic transition in the infrared range indicates a new electronic structure at the interface compared to the individual components. The intensity of this electronic excitation serves as a measure for the interface area indicating a linear increase with MoO3 concentration. Deposition onto cooled substrates results in smaller agglomerates, and thus yields a higher efficiency.